Selective separation and recovery of lithium, nickel, MnO2, and Co2O3 from LiNi0.5Mn0.3Co0.2O2 in spent battery. (January 2022) - He, Hongping; Feng, Junli; Gao, Xiaofeng; Fei, Xunchang
Abstract: The recovery of valuable metals from the LiNi0·5 Mn0·3 Co0·2 O2 in spent batteries deserves more attention. We report a series of feasible procedures to selectively recover the four metals (Li, Ni, Mn, and Co) using a combination of hydrometallurgical and pyrometallurgyical processes. Firstly, oxalic acid is used to dissolve Li and precipitate the other three metals in oxalate forms. It is found that under the optimal condition, about 98% of the Li is dissolved, and on average 93% of the other three metals are transformed to precipitated oxalates. The oxalates are then transformed to NiO·Mn2 O3 ·Co3 O4 by being calcinated at 723 K under atmospheric environment. The selective recovery of NiO·Mn2 O3 ·Co3 O4 can be achieved by using H2 SO4 under three different conditions. The first step is to use H2 SO4 to selectively dissolve CoO from the Co3 O4 . Then the combination of H2 SO4 and ultrasound is adopted to dissolve NiO, during which the ultrasound destroys the surficial oxide film on the NiO. Afterwards, the Mn2 O3 is transformed to MnO2 and Mn 2+ in heated H2 SO4 . The Co, Ni and Mn ions are dissolved in a sequence, which facilitates their separation and recovery. As the main components of the final residual solids, Co2 O3 and MnO2 present in distinctly different sizes and shapes, which are beneficial for their separation and direct usage. Highlights: Four metals in LiNi0·5 Mn0·3 Co0·2 O2 are selectively recovered. A hydrometallurgical and pyrometallurgyical combined process is developed. Oxalic acid dissolves Li and precipitates other three metals in oxalate forms. The precipitated oxalates are transformed to NiO·Mn2 O3 ·Co3 O4 for treatment. NiO·Mn2 O3 ·Co3 O4 is selectively recovered by H2 SO4 under different conditions.